Respostas

2014-06-29T21:38:03-03:00
Imagem 1 - (\frac{3}{4}) ^{0} - \frac{3}{2} = 1- \frac{3}{2} =- \frac{1}{2}

Imagem 2 (se for um quadrado) A=l^{2}  \\ 5=l^{2}  \\ l= \sqrt{5}  \\ l=2,24,aproximadamente

imagem 3 c)     V= a^{3}  \\ 0,064= a^{3}  \\ a= \sqrt[3]{0,064}  \\ a= \sqrt[3]{ 0,4^{3} }  \\ a=0,4
               
               d) V= a^{3} \\ 4,096=a^{3} \\ a= \sqrt[3]{4,096} \\ a= \sqrt[3]{ 1,6^{3} } \\ a=1,6

imagem 4 d)  \sqrt[4]{\frac{81}{16} }   \\  \sqrt[4]{ \frac{ 3^{4} }{ 2^{4} } }  \\ = \frac{3}{2}
             
 
                e)  \sqrt[5]{ \frac{32}{243} }  \\  \sqrt[5]{ \frac{ 2^{5} }{ 3^{5} } }  \\ = \frac{2}{3}